Faktor-Faktor Yang Mempengaruhi Minat Berwirausaha - Widya Nuriyanti; Dellia Mila Vernia; Lusiana Wulansari; Lengsi Manurung; Iramdan Iramdan (Jurnal Ilmiah Wahana Pendidikan, 2022)
The purpose of this study was to determine the effect of capital on interest in entrepreneurship, influence of family environment on interest in entrepreneurship, influence of technological ability on interest in entrepreneurship and the influence of capital, family environment, technological ability on interest in entrepreneurship in vocational students in Bekasi Regency. The sample was 127 students from 2 vocational schools in Bekasi Regency. The methodology used was a quantitative method using SPSS 21. The data is taken through a questionnaire and test assumptions. The assumption test included validity and reliability tests. Based on data processing, it showed that capital had an effect on interest in entrepreneurship, family environment on interest in entrepreneurship, technological ability affected interest in entrepreneurship and the influenced of capital, and capital, family environment, technological ability affected interest in entrepreneurship in vocational students in Bekasi Regency